Poza głosem. Postać Fenelli w świetle wystawień warszawskich z 1831 roku - Kaminiczna, Natalia (Poznańskie Studia Polonistyczne. Seria Literacka, 2022)
The article is an attempt to describe an operatic figure deprived of a voice. Following the views of Thrasybulos G. Georgiades, who believes that an operatic character differs from a literary or a dramatic one in that it constitutes a kind of symbiosis between person and sound, the author tries to characterise a mute character. She analyses the Warsaw stagings of Daniel Auber’s opera Masaniello ou La muette de Portici from 1831. Additionally, by activating the visual imagination and relying on iconographic and book sources (including Mimika [Facial expression] by Wojciech Bogusławski), the author reconstructs the character of Fenella in the interpretation of Antonina Palczewska in order to be able to investigate how this character functioned on stage. Such a procedure allowed for an in-depth analysis of the operatic figure devoid of a voice and created by means of a combination of facial expressions and gestures. The study also takes into account the circumstances and problems related to the performance of this opera during the November Uprising.